Pengaruh Efisiensi Operasional terhadap Profitabilitas Sektor Perbankan - Masdupi, Erni (Jurusan Manajemen Fakultas Ekonomi Universitas Negeri Padang, 2014)
The objective of this study is to examine the effect of capital adequacy ratio (CAR), operation expense to operation revenue (BOPO), loan to deposit ratio (LDR), and non performing loan (NPL) toward profitabily (return on asset—ROA) of listed companies in Indonesia Stock Exchange (IDX). Populatioon of this study is all banking that listed in IDX in the periode of 2007 till 2010. Based on purposive sampling 96 companies-years were selected. To answer the research question, multiple regresion was used. This study showed that CAR and LDR had insignificant effects on ROA while BOPO and NPL significantly and negatively affected ROA of listed companies on IDX.